Oxide electrode for lithium ion battery and preparation method of oxide electrode

The time to shorten the solid synthesis through laser heating technology solves the problem of low production efficiency and poor electrochemical properties in traditional methods, and realizes the efficient preparation of materials and excellent electrochemical properties.

CN119349638APending Publication Date: 2025-01-24UNIV OF SHANGHAI FOR SCI & TECH

Patent Information

Application Number
CN202411463979.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The traditional solid-phase synthesis of titanium niobium oxides has low production efficiency, and high-temperature calcination affects the crystal growth of the material, resulting in poor electrochemical performance.

Method used

Use laser heating instead of traditional burning heating. By accurately control the temperature and rapid heating up, shorten the synthesis time of solid phase, and improve the electrochemical performance of the material.

Benefits of technology

Significantly shortened the time of solid -phase synthesis, improved the multiplier performance and circulation performance of the material, improved the preparation efficiency, and formed a small and uniform particle size, high -quality high -quality material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349638A_ABST
    Figure CN119349638A_ABST
Patent Text Reader

Abstract

The invention discloses an oxide electrode for a lithium ion battery and a preparation method of the oxide electrode, and belongs to the technical field of lithium ion batteries. The preparation method of the titanium-niobium oxide negative electrode material comprises the following steps: weighing corresponding titanium dioxide powder and niobium pentoxide powder according to the chemical dosage ratio of TixNbyO2x + 2.5 y, putting the titanium dioxide powder and the niobium pentoxide powder into a mortar, fully grinding, uniformly mixing to obtain a precursor, uniformly coating and flatly paving the precursor on a slide, putting the slide under laser heating equipment, and carrying out high-temperature sintering to obtain the titanium-niobium oxide negative electrode material. And finally, preparing the product into a pole piece assembled battery, and carrying out electrochemical test on the pole piece assembled battery. According to the method, the solid-phase synthesis time is remarkably shortened through laser heating, the rate capability and the cycle performance of the battery are improved, and the preparation efficiency of the material is improved on the basis of ensuring high-quality formed phase and fine and uniform particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an oxide electrode for lithium ion batteries and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have become an indispensable part of energy storage due to their excellent energy density and long cycle life. In order to overcome the limitations of traditional lithium-ion battery anode materials and further improve battery performance, titanium niobium oxide (TiNbO) x Nb y O 2x+2.5y ) has emerged as a new type of material with fast charging capabilities and has become a research focus.

[0003] Titanium niobium oxide is used as a negative electrode material in lithium ion (Li + ) during the embedding and de-embedding process, it exhibits excellent structural stability and high cycle stability while maintaining a high energy density. The high working potential of titanium niobium oxide (~1.6V vs Li + / Li), effectively inhibiting the formation of lithium dendrites and significantly enhancing the safety of the battery, thus providing an important scientific basis and practical path for the innovation of lithium-ion battery technology. Most titanium niobium oxides (Ti2Nb 10 O 29 For example, the crystal structure of Li is a monoclinic phase structure. The crystal growth changes with the increase of temperature. When the temperature reaches above 1300℃, an orthorhombic phase structure will be generated. Compared with the monoclinic phase, it has a better structural symmetry. + In terms of transmission, it has more regular channels, and this feature is undoubtedly more conducive to the performance of lithium storage in titanium niobium oxide.

[0004] The traditional solid-phase synthesis method of titanium niobium oxide requires a long-term high-temperature (>1300°C) calcination of a mixed precursor of titanium and niobium oxides, so the production efficiency is relatively low. At the same time, too high a calcination temperature will cause the crystal cell volume to increase when the titanium niobium oxide crystal grows toward the orthorhombic phase, thus making the originally regular Li + The transmission channel grows, so that its excellent electrochemical performance cannot be normally exerted. For example: Chinese patent CN106025285A discloses a spherical titanium niobate electrode material and its preparation method, first dissolving the niobium source and the titanium source in an organic solvent respectively, mixing and heating to obtain a precipitate, washing and drying the precipitate, and calcining to obtain the product. Chinese patent CN112103493A discloses a preparation method of niobium titanium composite oxide, a negative electrode material for lithium batteries, first dissolving the titanium source and the niobium source in a dispersant, then performing a solvent thermal reaction, washing and drying, and calcining in a muffle furnace to obtain a product.

[0005] Therefore, it is necessary to develop a rapid synthesis method for lithium-ion battery oxide electrodes to improve electrochemical performance and increase production efficiency. Summary of the invention

[0006] The purpose of the present invention is to provide an oxide electrode for lithium-ion batteries and a preparation method thereof, so as to solve the problem that the above-mentioned solid-phase synthesis method of titanium niobium oxide has low production efficiency and its calcination process affects the crystal growth of titanium niobium oxide, resulting in poor electrochemical performance of titanium niobium oxide as a negative electrode of lithium batteries. The present invention significantly shortens the solid-phase synthesis time through laser heating, improves the rate performance and cycle performance of the battery, and improves the preparation efficiency of the material on the basis of ensuring high-quality phase formation and small and uniform particle size.

[0007] To achieve the above object, the present invention provides a method for preparing an oxide electrode for a lithium ion battery in a first aspect, comprising the following steps:

[0008] S1, according to Ti x Nb y O 2x+2.5y According to the chemical dosage ratio, the corresponding TiO2 powder and Nb2O5 powder are weighed, ground sufficiently, and mixed evenly to obtain a precursor;

[0009] S2, evenly spreading the precursor on a slide, and then placing it under a laser heating device for sintering to obtain titanium niobium oxide.

[0010] Titanium Niobium Oxide (Ti x Nb y O 2x+2.5y) As a new type of material with fast charging capability, it has advantages in structural stability and cycle stability. However, in order to prepare titanium niobium oxide with an orthorhombic phase structure, the commonly used method is solid phase synthesis. The specific process of solid phase synthesis is generally to mix and heat a titanium source and a niobium source to obtain a precipitate, and then wash and dry the precipitate and calcine it to obtain a product. The present invention has found that in the calcination process of the traditional solid phase reaction, on the one hand, the calcination time is long, which affects the production efficiency. On the other hand, the calcination process affects the crystal orthorhombic phase growth process of titanium niobium oxide, and the unit cell volume increases, which in turn affects the electrochemical performance of titanium niobium oxide as a negative electrode of a lithium battery. In response to this problem, the present invention uses laser heating to replace traditional calcination heating. Laser heating can accurately control the temperature and directly act on the heated part without affecting other parts. It is very important for forming materials with a specific crystal structure. Laser heating has the characteristics of rapid heating. Rapid heating helps to accelerate the reaction process. At the same time, rapid cooling also helps to retain the microstructure of the material and prevent the performance of titanium niobium oxide from being degraded due to long-term high-temperature calcination treatment. In addition, during the laser heating process, by adjusting the movement speed and path of the laser beam, the uniformity of the temperature distribution on the sample surface can be achieved. Uniform heating helps to form a consistent crystal structure, which is crucial for the consistency and reliability of the negative electrode material. If there are uneven areas inside the material, then these areas may become weak links in the operation of the battery and affect the stability of the battery.

[0011] Preferably, the grinding method in step S1 is one of manual grinding and ball mill grinding.

[0012] When the present invention uses manual grinding, firstly, TiO2 powder and Nb2O5 powder are placed in a mortar, and then manually ground.

[0013] Preferably, in step S1, Ti x Nb y O 2x+2.5y The crystal spatial structure is Wadsley-Roth phase structure.

[0014] Preferably, in step S1, Ti x Nb y O 2x+2.5y The x value is 1 to 2, and the y value is 2 to 24.

[0015] Preferably, in step S1, Ti x Nb y O 2x+2.5y The x values ​​are 1 and 2, and the y values ​​are 2, 10, and 24.

[0016] Preferably, the sintering conditions in step S2 are: in an air atmosphere, the power of the laser heating equipment is 200W to 500W, the scanning speed is 120Hz, the scanning width is 5mm, the pulse frequency is 1000Hz, the wire feeding speed is 3mm / s, and the sintering time is 30s to 60s.

[0017] Preferably, the paving thickness of the precursor in step S2 is 1 to 2.5 mm.

[0018] Preferably, the material of the specimen slide in step S2 is one of a ceramic sheet, a titanium sheet, and a stainless steel sheet.

[0019] The selection of the slide in the present invention is mainly based on the boiling point of the precursor to be sintered.

[0020] Preferably, the laser heating device in step S2 comprises a box body and a display panel and operation keys arranged on the surface of the box body, and a laser heating device is placed in the hollow space inside the box body;

[0021] The laser heating device is a cubic structure. A horizontal ball screw and a vertical ball screw are arranged on the top of the cubic structure. Both the horizontal ball screw and the vertical ball screw are driven by a stepper motor. Slides are arranged at the bottom of both ends of the horizontal ball screw. The slides are slidably connected to the top of the cubic structure through slide rails. The slides are sleeved on the vertical ball screw to drive the horizontal ball screw to move along the direction of the slide rails. A clamp is sleeved on the horizontal ball screw, and a laser gun head is fixed to the bottom end of the clamp.

[0022] In the process of using the laser heating device of the present invention, the carrier sheet with the precursor is first placed in a square structure, and the horizontal ball screw and the vertical ball screw are driven by a stepper motor to realize the movement on the x-axis and the y-axis until the laser gun head is aligned with the carrier sheet, and the laser heating process of the precursor is started. The laser heating process in the present invention is as short as tens of seconds, and the heating time is very short compared with the traditional calcination process, and it is not easy to affect the crystal growth process of titanium niobium oxide. The material with fine and uniform particle size and high-quality phase formation is prepared, and it has excellent electrochemical properties as the negative electrode material of lithium ion battery.

[0023] The second aspect of the present invention provides an oxide electrode for a lithium ion battery, which is prepared by the above preparation method.

[0024] Therefore, the present invention adopts the above-mentioned oxide electrode for lithium ion battery and the preparation method thereof, which has the following beneficial effects:

[0025] 1. The present invention significantly shortens the solid phase synthesis time through laser heating, improves the rate performance and cycle performance of the battery, and improves the material preparation efficiency while ensuring high-quality phase formation and small and uniform particle size.

[0026] 2. In the laser rapid sintering process of the present invention, since the temperature of laser heating is high and can achieve rapid temperature rise, the thermal motion of oxygen atoms is intensified, making it easier for them to escape from the lattice, thereby forming oxygen vacancies, thereby increasing the electronic conductivity of the material and helping to improve the charge transfer performance of the material; in addition, the appearance of oxygen vacancies provides channels and space for the diffusion of ions, accelerates the migration rate of ions in the electrode material, and improves the rate performance of the electrode.

[0027] 3. The laser heating of the present invention helps to form a denser material structure and reduce porosity and other defects, which helps to improve the conductivity of the material and the lithium ion transmission efficiency, thereby improving the overall performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the overall structure of the box;

[0029] Figure 2 It is a structural schematic diagram of a laser heating device;

[0030] Figure 3 XRD patterns of titanium niobium oxide products prepared in Example 1 and Comparative Example 1;

[0031] Figure 4 The charge and discharge curve of the titanium niobium oxide negative electrode material prepared in Example 1;

[0032] Figure 5 The rate performance diagram of the titanium niobium oxide negative electrode material prepared in Example 1 and Comparative Example 1;

[0033] Figure 6 This is a rate performance diagram of the titanium niobium oxide negative electrode material prepared in Example 2;

[0034] Figure 7 This is a SEM image of the titanium niobium oxide negative electrode material prepared in Example 2;

[0035] Figure 8 This is a SEM image of the titanium niobium oxide negative electrode material prepared in Example 3;

[0036] Fig. 9 This is the cycle performance curve of the titanium niobium oxide negative electrode material prepared in Example 3;

[0037] In the figure: 1. Box body; 101. Display panel; 102. Operation button; 2. Heating device; 201. Horizontal ball screw; 202. Depth ball screw; 203. Ball screw stepper motor; 204. Clamp; 205. Laser gun head. DETAILED DESCRIPTION

[0038] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0039] Example 1

[0040] A rapid synthesis method for an oxide electrode for a lithium ion battery, comprising the following steps:

[0041] Step (1), according to Ti2Nb 10 O 29 According to the chemical dosage ratio, 1597.32 mg TiO2 powder and 13290.49 mg Nb2O5 powder were weighed, placed in an agate mortar, and manually ground for 40 min to obtain a precursor after mixing them evenly;

[0042] Step (2), take out the precursor prepared in the above step, evenly spread it on a titanium sheet of 20 mm × 20 mm in size with a thickness of 1.5 mm, and then place the titanium sheet in a laser heating device (such as Figure 2 ) for position calibration, after setting the laser gun head feeding program, high temperature solid phase sintering was carried out with a peak heating power of 300W, a scanning speed of 120Hz, a scanning width of 5mm, a pulse frequency of 1000Hz, a wire feeding speed of 3mm / s, and a sintering time of 40s. Finally, a titanium niobium oxide product was obtained, and its XRD spectrum is shown in Figure 3 As shown. Figure 3 It can be seen that Ti2Nb 10 O 29 The product has been successfully prepared.

[0043] Step (3), transferring the titanium niobium oxide product obtained in the above step to an agate mortar and manually grinding it for 30 minutes to obtain an electrode active material, mixing the electrode active material, conductive carbon black, and adhesive (4wt% polyvinylidene fluoride N-methylpyrrolidone solution) in a mass ratio of 8:1:1, specifically 192mg:24mg:600mg, and placing it in a high-speed paddle machine, stirring it at different powers of 2200W, 2000W, and 1800W three times to form a slurry, using an ion battery coating machine to coat the slurry on the surface of a copper foil (70mm×150mm), and then placing it in a constant temperature vacuum oven at 80°C to dry for 10 hours, and then using a cutter with a diameter of 10mm to cut out the electrode piece.

[0044] Step (4), in a vacuum glove box, a metal lithium sheet is used as a counter electrode, and a ternary 1M LiPF6 / (EC:DC:DMC=1:1:1) ester solution is selected as an electrolyte to assemble a CR2023 button cell, and a 1.0-3.0V (V vs.Li + / Li) voltage range, and electrochemical tests were performed on it at current densities of 0.5C, 1C, 2C, 5C, 10C, and 20C, and its electrochemical performance was analyzed. The charge and discharge curves were measured as follows: Figure 4 As shown, its rate performance is as follows Figure 5 As shown. Figure 4 It can be seen that the titanium niobium oxide prepared in Example 1 is used as a negative electrode material for lithium ion batteries, and the charge and discharge capacity does not change significantly after three charge and discharge cycles, indicating that the titanium niobium oxide prepared in the present invention has good stability.

[0045] Example 2

[0046] A rapid synthesis method for an oxide electrode for a lithium ion battery, comprising the following steps:

[0047] Step (1), according to the chemical dosage ratio of TiNb2O7, weigh 798.66 mg of TiO2 powder and 2658.1 mg of Nb2O5 powder, put them into an agate mortar, and grind them manually for 40 minutes to obtain a precursor after mixing them evenly;

[0048] Step (2), take out the precursor prepared in the above step, evenly spread it on a titanium sheet of 20 mm × 20 mm in size with a thickness of 1.5 mm, and then place the titanium sheet in a laser heating device (such as Figure 2 ) for position calibration, after setting the laser gun head feeding program, high temperature solid phase sintering was carried out with a peak heating power of 450W, a scanning speed of 120Hz, a scanning width of 5mm, a pulse frequency of 1000Hz, a wire feeding speed of 3mm / s, and a sintering time of 50s. Finally, a titanium niobium oxide product was obtained, and its SEM image is shown in Figure 7 As shown, from Figure 7 It can be seen that the product particle size is about 100-300nm.

[0049] Step (3), transferring the titanium niobium oxide product obtained in the above step to an agate mortar and manually grinding it for 30 minutes to obtain an electrode active material, mixing the active material, conductive carbon black, and adhesive (4wt% polyvinylidene fluoride N-methylpyrrolidone solution) in a mass ratio of 8:1:1, specifically 192mg:24mg:600mg, and placing it in a high-speed paddle machine, stirring it at different powers of 2200W, 2000W, and 1800W three times to form a slurry, using an ion battery coating machine to coat the slurry on the surface of a copper foil (70mm×150mm), then placing it in a constant temperature vacuum oven at 80°C and drying it for 10 hours, and then using a cutter with a diameter of 10mm to cut out the electrode piece.

[0050] Step (4), in a vacuum glove box, a metal lithium sheet is used as a counter electrode, and a ternary 1M LiPF6 / (EC:DC:DMC=1:1:1) ester solution is selected as an electrolyte to assemble a CR2023 button cell, and a 1.0-3.0V (V vs.Li + / Li) voltage range, and electrochemical tests were performed on it at current densities of 0.5C, 1C, 2C, 5C, 10C, and 20C, and its electrochemical performance was analyzed. Its rate performance was measured as follows: Figure 6 shown.

[0051] Example 3

[0052] A rapid synthesis method for lithium ion battery oxide electrodes, the steps are as follows:

[0053] Step (1), according to TiNb 24 O 62 According to the chemical dosage ratio, 79.87 mg TiO2 powder and 3189.72 mg Nb2O5 powder were weighed, placed in an agate mortar, and manually ground for 40 min to mix them evenly to obtain a precursor;

[0054] Step (2), take out the precursor prepared in the above step, evenly spread it on a titanium sheet of 20 mm × 20 mm in size with a thickness of 1.5 mm, and then place the titanium sheet in a laser heating device (such as Figure 2 ) for position calibration, after setting the laser gun head feeding program, high temperature solid phase sintering was carried out with a peak heating power of 200W, a scanning speed of 120Hz, a scanning width of 5mm, a pulse frequency of 1000Hz, a wire feeding speed of 3mm / s, and a sintering time of 60s. Finally, a titanium niobium oxide product was obtained, and its SEM spectrum is shown in Figure 8 As shown;

[0055] Step (3), transferring the titanium niobium oxide product obtained in the above step to an agate mortar and manually grinding it for 30 minutes to obtain an electrode active material, mixing the active material, conductive carbon black, and adhesive (4wt% polyvinylidene fluoride N-methylpyrrolidone solution) in a mass ratio of 8:1:1, specifically 192mg:24mg:600mg, and placing it in a high-speed paddle machine, stirring it at different powers of 2200W, 2000W, and 1800W three times to form a slurry, using an ion battery coating machine to coat the slurry on the surface of a copper foil (70mm×150mm), then placing it in a constant temperature vacuum oven at 80°C and drying it for 10 hours, and then using a cutter with a diameter of 10mm to cut out the electrode piece.

[0056] Step (4), in a vacuum glove box, a metal lithium sheet is used as a counter electrode, and a ternary 1M LiPF6 / (EC:DC:DMC=1:1:1) ester solution is selected as an electrolyte to assemble a CR2023 button cell, and a 1.0-3.0V (V vs.Li + / Li) voltage range, and electrochemical tests were performed on it at current densities of 0.5C, 1C, 2C, 5C, 10C, and 20C, and its electrochemical performance was analyzed. The cycle performance curve was measured as follows: Fig. 9 shown.

[0057] from Fig. 9 It can be seen that the specific capacity of the titanium niobium oxide prepared in Example 3 remains basically unchanged after multiple cycles, indicating that it has good cycle stability. The high specific capacity value indicates that the material has good lithium storage performance.

[0058] Example 4

[0059] like Figure 1 and Figure 2 As shown, the structure of the laser heating equipment is as follows:

[0060] The laser heating device comprises a housing 1, a display panel 101 and an operation key 102 arranged on the surface of the housing 1, and a laser heating device 2 is placed in the hollow interior of the housing 1;

[0061] The laser heating device 2 is a cubic structure, and a horizontal ball screw 201 and a vertical ball screw 202 are arranged on the top of the cubic structure. The horizontal ball screw 201 and the vertical ball screw 202 are driven by a stepper motor 203. Slides are arranged at the bottom of both ends of the horizontal ball screw 201. The slides are slidably connected to the top of the cubic structure through slide rails. The slides are sleeved on the vertical ball screw 202 to drive the horizontal ball screw 201 to move along the slide rail. A clamp 204 is sleeved on the horizontal ball screw 201, and a laser gun head 205 is fixed to the bottom end of the clamp 204.

[0062] Comparative Example 1

[0063] A method for preparing titanium niobium oxide for lithium ion batteries comprises the following steps:

[0064] Step (1), according to Ti2Nb 10 O 29 According to the chemical dosage ratio, 1597.32 mg TiO2 powder and 13290.49 mg Nb2O5 powder were weighed, placed in an agate mortar, and manually ground for 40 min to obtain a precursor after mixing them evenly;

[0065] Step (2), transferring the precursor prepared in the above step into a corundum crucible with a wall thickness of 3.5 mm and a size of 100 mm×30 mm×20 mm;

[0066] Step (3), placing the corundum crucible containing the precursor in the above step in a muffle furnace, setting a heating program and performing high-temperature solid phase synthesis on it:

[0067] P1, after 10 h, the furnace temperature was raised from room temperature to 1300 °C;

[0068] P2, maintain 1300℃ for 10h;

[0069] P3, after the heat preservation is finished, the furnace is naturally cooled to room temperature;

[0070] Step (4), the cooled titanium niobium oxide crude product is taken out from the muffle furnace, transferred to an agate mortar, and manually ground for 30 minutes to finally obtain a titanium niobium oxide product with uniform and fine particle size, and its XRD spectrum is as follows: Figure 3 As shown;

[0071] Step (5), using the titanium niobium oxide product obtained in the above step as an electrode active material, the electrode active material, conductive carbon black, and bonding agent (4wt% polyvinylidene fluoride N-methylpyrrolidone solution) are mixed in a mass ratio of 8:1:1, specifically 192mg:24mg:600mg, and placed in a high-speed paddle machine, and stirred at different powers of 2200W, 2000W, and 1800W three times to form a slurry, and an ion battery coating machine is used to coat the slurry on the surface of a copper foil (70mm×150mm), and then placed in a constant temperature vacuum oven at 80°C for drying for 10 hours, and then a cutter with a diameter of 10mm is used to cut out the electrode piece.

[0072] Step (6), in a vacuum glove box, a metal lithium sheet is used as a counter electrode, and a ternary 1M LiPF6 / (EC:DC:DMC=1:1:1) ester solution is selected as an electrolyte to assemble a CR2023 button cell, and a 1.0-3.0V (V vs.Li + / Li) voltage range, and electrochemical tests were performed on it at current densities of 0.5C, 1C, 2C, 5C, 10C, and 20C, and its electrochemical performance was analyzed. Its rate performance is as follows Figure 5 shown.

[0073] from Figure 5 It can be seen that under all rate conditions, the specific capacity of Example 1 and Comparative Example 1 decreases with the increase of the number of cycles, but the specific capacity of Example 1 is significantly higher than that of Comparative Example 1, indicating that the cycle stability of Example 1 is better. Under different rates, the specific capacity of Example 1 decreases slowly, which also indicates that the cycle stability of Example 1 is better than that of Comparative Example 1.

[0074] Comparative Example 2

[0075] A rapid synthesis method for an oxide electrode of a lithium ion battery, wherein the synthesis steps are different from those of Example 1 in that the peak heating power of the laser gun head is 800W.

[0076] Comparative Example 3

[0077] A rapid synthesis method for an oxide electrode for a lithium ion battery, wherein the synthesis steps are different from those of Example 1 in that the sintering time is 100 seconds.

[0078] The cycle performances of the titanium niobium oxides prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1.

[0079] Specific capacity retention rate after 400 cycles = specific capacity after 400 cycles / initial specific capacity × 100%

[0080] Table 1 Cycle performance test results

[0081]

[0082] Therefore, the present invention adopts the above-mentioned oxide electrode for lithium ion batteries and the preparation method thereof to prepare titanium niobium oxide with high-quality phase, fine and uniform particle size, simple operation process, environmental protection and pollution-free, suitable for large-scale industrial production, and compared with the product obtained by the traditional titanium niobium oxide preparation method, the prepared product shows better electrochemical performance while ensuring better stability and uniformity.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an oxide electrode for a lithium ion battery, characterized in that: The following steps are involved: S1, according to Ti x Nb y O 2x+2.5y According to the chemical dosage ratio, the corresponding TiO2 powder and Nb2O5 powder are weighed, ground sufficiently, and mixed evenly to obtain a precursor; S2, evenly spreading the precursor on a slide, and then placing it under a laser heating device for sintering to obtain titanium niobium oxide.

2. The method for preparing an oxide electrode for a lithium ion battery according to claim 1, characterized in that: The grinding method in step S1 is one of manual grinding and ball mill grinding.

3. The method for preparing an oxide electrode for a lithium ion battery according to claim 1, characterized in that: In step S1, Ti x Nb y O 2x+2.5y The crystal spatial structure is Wadsley-Roth phase structure.

4. The method for preparing an oxide electrode for a lithium ion battery according to claim 1, characterized in that: In step S1, Ti x Nb y O 2x+2.5y The x value is 1 to 2, and the y value is 2 to 24.

5. The method for preparing an oxide electrode for a lithium ion battery according to claim 1, characterized in that: The sintering conditions in step S2 are: in an air atmosphere, the power of the laser heating equipment is 200W to 500W, the scanning speed is 120Hz, the scanning width is 5mm, the pulse frequency is 1000Hz, the wire feeding speed is 3mm / s, and the sintering time is 30s to 60s.

6. The method for preparing an oxide electrode for a lithium ion battery according to claim 1, characterized in that: The paving thickness of the precursor in step S2 is 1 to 2.5 mm.

7. The method for preparing an oxide electrode for a lithium ion battery according to claim 1, characterized in that: In step S2, the material of the specimen slide is one of a ceramic sheet, a titanium sheet, and a stainless steel sheet.

8. The method for preparing an oxide electrode for a lithium ion battery according to claim 1, characterized in that: The laser heating device in step S2 includes a box body and a display panel and operation keys arranged on the surface of the box body, and a laser heating device is placed in the hollow space inside the box body; The laser heating device is a cubic structure. A horizontal ball screw and a vertical ball screw are arranged on the top of the cubic structure. Both the horizontal ball screw and the vertical ball screw are driven by a stepper motor. Slides are arranged at the bottom of both ends of the horizontal ball screw. The slides are slidably connected to the top of the cubic structure through slide rails. The slides are sleeved on the vertical ball screw to drive the horizontal ball screw to move along the direction of the slide rails. A clamp is sleeved on the horizontal ball screw, and a laser gun head is fixed to the bottom end of the clamp.

9. An oxide electrode for a lithium ion battery, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Spherical titanium niobate electrode material and preparation method thereof

    CN106025285A

  • Preparation method of lithium battery negative electrode material titanium-niobium composite oxide

    CN112103493A

Cited By

  • Materials, devices, and methods with compositions for oxide ceramics for extreme environments

    WO2026165421A3